Establishing a stable society for the sake of ecclesiastical expansion in a frontier capital (King William’s Town) in the Eastern Cape: the pensioners and their village between 1855 and 1861 - Hofmeyr, JW; Hofmeyr, GS (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
For many different reasons, the Eastern Cape area has long been and remains oneof the strong focus points of general, political and ecclesiastical historians. In this first article of a series on a frontier capital (King William’s Town) in the Eastern Cape,I wish to focus on a unique socio economic aspect of the fabric of the Eastern Capesociety in the period between 1855 and 1861 i.e. the establishment of a Pensioners’ Village. It also touches on certain aspects of the process of colonization in the Eastern Cape. Eventually all of this had, besides many other influences, also an influence on the further expansion of Christianity in the frontier context of the Eastern Cape. In a next article the focus will therefore be on a discussion and analysis of the expansion of missionary work in this frontier context against the background of the establishment of the Pensioners’ Village.